Nanobody-Based Delivery Systems for Diagnosis and Targeted Tumor Therapy - Hu, Yaozhong; Liu, Changxiao; Muyldermans, Serge (Frontiers in Immunology, 2017)
The development of innovative targeted therapeutic approaches are expected to surpass the efficacy of current forms of treatments and cause less damage to healthy cells surrounding the tumor site. Since the first development of targeting agents from hybridoma’s, monoclonal antibodies (mAbs) have been employed to inhibit tumor growth and proliferation directly or to deliver effector molecules to tumor cells. However, the full potential of such a delivery strategy is hampered by the size of mAbs, which will obstruct the targeted delivery system to access the tumor tissue. By serendipity, a new kind of functional homodimeric antibody format was discovered in camelidae, known as heavy-chain antibodies (HCAbs). The cloning of the variable domain of HCAbs produces an attractive minimal-sized alternative for mAbs, referred to as VHH or nanobodies (Nbs). Apart from their dimensions in the single digit nm range, the unique characteristics of Nbs combine a high stability and solubility, low immunogenicity and excellent affinity and specificity against all possible targets including tumor markers. This stimulated the development of tumor targeted therapeutic strategies. Some autonomous Nbs have been shown to act as antagonistic drugs, but more importantly, the targeting capacity of Nbs has been exploited to create drug delivery systems. Obviously, Nb-based targeted cancer therapy is mainly focused towards extracellular tumor markers, since the membrane barrier prevents antibodies to reach the most promising intracellular tumor markers. Potential strategies, such as lentiviral vectors and bacterial Type 3 Secretion System, are proposed to deliver target-specific Nbs into tumor cells and to block tumor markers intracellularly. Simultaneously, Nbs have also been employed for in vivo molecular imaging to diagnose diseased tissues and to monitor the treatment effects. Here we review the state of the art and focus on recent developments with Nbs as targeting moieties for drug delivery systems in cancer therapy and cancer imaging.